Dynamics of technical efficiency of sugar mills in India: Stochastic Frontier Approach - Kumar, Shiv; Abdulla, Abdulla (The Indian Journal of Agricultural Sciences, 2020)
Using an annual survey industries unit level data pertaining to year 2014-15 from India, this paper examines the technical efficiency of sugar mills. A Stochastic Production Frontier (SFA) approach has been applied to measure technical efficiency of 490 sugar mills. The empirical results show that on an average sugar mills have 54% technical efficient, despite presence of considerable variations of technical efficiency among the selected states. This paper establishes a repertoire of management regimes varying in technical efficiency. It further reveals a significant difference in organization specific average technical efficiency of sugar mills across states. Overall, sugar mills are running under decreasing returns to scale. The emergent suggestion is to bring improvement in capital input use which is more effective than the labour input and augmentation in liability asset ratio. The management of less efficient mills needs to imbibe the best practices in terms of technology, policy and institutions of more efficient mills operating in other states.